Badania logiczne prowadzone w Uniwersytecie Poznańskim w latach 1945 - 1955 - Murawski, Roman; Pogonowski, Jerzy (Investigationes Linguisticae, 2007)
This paper is a synopsis of a more comprehensive work presented at the conference 50 years of Studia Logica in 2003. The full English version of the text will be published elsewhere. The text below is devoted to the presentation of logical investigations carried out at the University of Poznań in the first decade after its reopening in 1945, i.e. at the time when and at the place where Studia Logica came into existence.